Optimization of residential Solar-Hydrogen Production as Remote Electrification Using HOMER in Nablus City - Aloudeh, Rahaf (My University, 2021)
Abstract The research paper investigates the optimum design of an off-grid PV-FC power system that is set to cover the electric load demand of residence in the city of Nablus, Palestine. The techno-economic performance of the optimum design is tested over number of parameters and specifications and based on real weather data and first-hand load profile of Al Masaken Al Sha’beya area in the city. The simulation model is designed and studied for optimization results using HOMER Pro Software. The developed simulations are run over the same conditions and parameters for three different models: PV arrays with hydrogen tank, PV arrays with battery storage system and PV arrays with both commentary units of hydrogen and battery storage. The main power of the hybrid system in the three models comes from the PV panels, where the FC and battery system are both considered as backup renewables to cover what shortage caused from different radiation levels. The optimization software HOMER in the paper proposes the system architecture and the statue que of the power control, and proposes feasible solutions over the three models that covers the load demand. The results demonstrate obvious compatibility of PV-BATT model, where the PV-FC shows better power saving and utilization of renewables. Keyword: Fuel cell, PV/Hydrogen, Hybrid power system, techno-economy optimization, HOMER.